1990-2008 yılları arasında kasko hasar ödemelerinin Türk Ekonomisindeki yeri - Çilesiz, Ufuk Yavuz (My University, 2010)
“1990 – 2008 Yılları Arasında Kasko Hasar Ödemelerinin Türk Ekonomisindeki Yeri” isimli çalışmamızda, ekonomik yönden kasko prim ödemelerinin ve hasar kayıplarının GSYİH’ YA pozitif ve negatif etkileri rakamsal olarak incelenerek değerlendirilmiştir. Bu amaçla ilk olarak risk ve sigorta prensipleri incelenmiştir. Burada sigortanın özellikleriyle sigorta işlemlerinin ortaya çıkmasındaki risk durumların, sigortanın temel işleyişi ve aracıları hakkında bilgiler sunulmuştur. Daha sonra bir sigorta türü olarak kasko, yapısı, özellikleri ve hasar uygulamaları incelenmiştir. Burada kasko sigortasının tanımı ve sınırlamaları, kasko sigortasında teminata dahil edilen ve edilmeyen riskler, sigorta türleri ve hasar tespitleri hakkında bilgiler sunulmuştur. Son olarak ise Türk Sigorta Sektörünün 1990–2008 yılları arasındaki kasko primleri ve hasar ödemelerinin ekonomideki yeri incelenmiştir. Burada Türk Sigorta Sektörünün makro planda gelişimi ve Türk Sigorta Sektörü içerisindeki kurumlar incelenmiştir. Ayrıca 1990 yılından başlayarak 2008 yılına kadar kasko primlerinin ekonomik yapısı sunulmuştur ve hasarların ekonomik yapısı yine bu yıllar arasında incelenerek bir dABSTRACT In this study named “The Place of Automobile Damage Insurance Payments in Turkish Economy between 1990-2008”, with economical view and in figures, the positive and negative effects of the automobile premium payments and losses through damages to the Gross National Products is examined and evaluated. With this purpose, firstly risk and insurance principals are examined. In this section, information is given about insurance clauses, risk cases where insurance transactions come out, and how insurance works in principle and intermediaries. Later, as a kind of insurance automobile insurance, its structure and properties and damage practises were examined. Here, information about definition of automobile insurance, its restrictions, risks covered and uncovered in the insurance policy, types of insurances and assessment of damages were presented. In the last section, the place of both automobile insurance premiums in Turkish Insurance Sector between 1990-2008 and damage payments in economoy are examined. Here the development of Turkish Insurance Sector in macro plan and institutions inside the sector are examined. Furthermore, beginning with 1990 until 2008 economical structure of of atomobile insurance premiums is presented. Economical structure of damages in these years is also examined and evaluated. eğerlendirmeye gidilmiştir.

In this study named “The Place of Automobile Damage Insurance Payments in Turkish Economy between 1990-2008”, with economical view and in figures, the positive and negative effects of the automobile premium payments and losses through damages to the Gross National Products is examined and evaluated. With this purpose, firstly risk and insurance principals are examined. In this section, information is given about insurance clauses, risk cases where insurance transactions come out, and how insurance works in principle and intermediaries. Later, as a kind of insurance automobile insurance, its structure and properties and damage practises were examined. Here, information about definition of automobile insurance, its restrictions, risks covered and uncovered in the insurance policy, types of insurances and assessment of damages were presented. In the last section, the place of both automobile insurance premiums in Turkish Insurance Sector between 1990-2008 and damage payments in economoy are examined. Here the development of Turkish Insurance Sector in macro plan and institutions inside the sector are examined. Furthermore, beginning with 1990 until 2008 economical structure of of atomobile insurance premiums is presented. Economical structure of damages in these years is also examined and evaluated.
Keywords: Ekonomi_Türkiye; Kasko; Sigortacılık